Teaching Mathematics with a focus on Sustainability: an interdisciplinary approach aligned with the 2030 Agenda - Possamai, Janaína Poffo; Pereira, Rafael Falco; Frenedozo, Rita de Cássia (Educação Matemática Debate, 2025)
This article presents a systematic review of theses and dissertations published between 2015 and 2024, aiming to identify methodological strategies that connect mathematics education to the promotion of sustainability, in alignment with the 2030 Agenda. The research, of a qualitative nature, analyzed studies on the development of educational practices that relate mathematical learning objectives to Education for Sustainable Development. The results show that the teaching strategies used link mathematical content to environmental issues through problem-solving and mathematical modeling, promoting an interdisciplinary and critical approach. The identified practices contribute to the formation of systemic and reflective competencies in students, aligned with the Sustainable Development Goals.